Differential Diagnosis of Urticarial Lesions - Matos, Ana Luísa; Figueiredo, Carolina; Gonçalo, Margarida (Frontiers in Allergy, 2022)
Urticaria is a mast cell-dependent disease, characterized by the presence of wheals, angioedema, or both in the absence of systemic symptoms. It is a common disease worldwide, with an important health burden especially in chronic situations, that last more than 6 weeks. Although urticaria is usually a straightforward diagnosis, some diseases presenting with urticarial lesions must be excluded, particularly urticarial vasculitis and auto-inflammatory syndromes. In these settings additional atypical features are often present (long-lasting lesions, bruising, fever, malaise, arthralgia), allowing the clinician to suspect a diagnosis other than urticaria. The authors propose an approach based on these atypical features, the presence or absence of systemic symptoms and on skin histopathology as well as some blood parameters.